Mathematical Disposition Scheme of Elementary School Students based on Adversity Quotient (AQ) - Mohammad Archi Maulyda; Vivi Rachmatul Hidayati; Awal Nur Kholifatur Rosyidah ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2022)
This research is motivated by the lack of public awareness of the importance of affective aspects in the world of education, especially mathematics. In mathematics, a positive attitude towards mathematics which includes self-confidence, flexibility, persistence, curiosity and appreciation of the role of mathematics is called a mathematical disposition. One of the internal factors that influence the mathematical disposition is Advesity Quotient (AQ) which has three levels, namely climber, camper and quitter. The purpose of this study is describe the mathematical disposition of students with AQ climbers, campers and quitters. The approach used in this research is qualitative with descriptive type. The instrument used is an aq questionnaire which is used to classify students' aq levels and an observation sheet which is used to determine students' mathematical dispositions. The research subjects were fifth grade students in the Mataram City area. The conclusions of this research are (1) Subjects with AQ climber have a mathematical disposition score of 90% can show all indicators of students' mathematical disposition, namely self-confidence, flexibility, persistence, curiosity and appreciation of the role of mathematics. (2) Subjects with AQ camper have a score of 57.5% mathematical disposition can show three indicators of students' mathematical disposition, namely self-confidence, curiosity and appreciation of the role of mathematics. (3) Subjects with AQ quitter have a mathematical disposition score of 41.5% that does not show a mathematical disposition at all.